Optimal Joint Source and Relay Beamforming for Parallel MIMO Relay Networks - Toding, Apriana; Khandaker, Muhammad; Rong, Yue (IEEE, 2010)
In this paper, we study the optimal structure of the source precoding matrix and the relay amplifying matrices for multiple-input multiple-output (MIMO) relay communication systems with parallel relay nodes. We show that both the optimal source precoding matrix and the optimal relay amplifyingmatrices have a beamforming structure. Using the optimal structure, a joint source and relay power loading algorithm is developed to minimize the mean-squared error (MSE) of the signal waveform estimation. Compared with existing algorithms for parallel MIMO relay networks, the proposed joint source and relay beamforming algorithm has a significant improvement in the system bit-error-rate performance.